2003
DOI: 10.1038/sj.leu.2403032
|View full text |Cite
|
Sign up to set email alerts
|

Downmodulation of ERK activity inhibits the proliferation and induces the apoptosis of primary acute myelogenous leukemia blasts

Abstract: MAP kinase/ERK kinase (MEK)-extracellular signal-regulated kinase (ERK) kinases are frequently activated in acute myelogenous leukemia (AML), and can have prosurvival function. The purpose of this study was to induce downmodulation of MEK-ERK activation in AML primary blasts in order to detect the effect on cell cycle progression and on the apoptosis of leukemic cells. We investigated 14 cases of AML with high ERK 1/2 activity and four cases with undetectable or very low activity. After 24 h incubation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 34 publications
6
69
1
Order By: Relevance
“…The MAPKs families consist of three subfamilies, namely ERK, JNK and p38 (Romos, 2008; Zhang & Liu, 2002). Numerous studies have focused on ERK1/2 inhibition leading to cancer cell death (Lunghi et al., 2003; Wang et al., 2010; Wu, Wong, Khosravi, Minden, & Penn, 2004). Furthermore, p38 MAPK plays a role in cell cycle arrest by activating cell cycle checkpoints (Feng et al., 2015; Thornton & Rincon, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The MAPKs families consist of three subfamilies, namely ERK, JNK and p38 (Romos, 2008; Zhang & Liu, 2002). Numerous studies have focused on ERK1/2 inhibition leading to cancer cell death (Lunghi et al., 2003; Wang et al., 2010; Wu, Wong, Khosravi, Minden, & Penn, 2004). Furthermore, p38 MAPK plays a role in cell cycle arrest by activating cell cycle checkpoints (Feng et al., 2015; Thornton & Rincon, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it is well known that the Erk 1/2 pathway is up regulated in most cases of AML. 33 Controls were represented by Jurkat cells treated with 80 nM 4a-Phorbol 12-myristate 13-acetate (PMA), a powerful activator of the Erk 1/2 pathway (see Figure 4a). Five out of nine patients, who were positive for MRP1, also had activated Erk 1/2 (Table 2).…”
Section: Down Regulation Of Ser 473 P-akt With Wortmannin Results Inmentioning
confidence: 99%
“…Previous studies using the MEK inhibitor PD98059 reported that inhibition of p-ERK was coupled with the induction of apoptosis. 5,22 We failed to demonstrate apoptosis induction after 24 h and even after extended incubation with 3 mM CI-1040. Only in a single sample, p-ERK inhibition was associated with induction of apoptosis.…”
Section: Figurementioning
confidence: 98%
“…p-ERK expression in refractory/relapsed AML samples MR Ricciardi et al with previous reports 5, 21,22 using Western blotting for analysis of p-ERK, we examined here, for the first time, clinical samples by FCM. FCM allows to better identify and quantify phosphoproteins in subpopulations of cells with undetectable or very low expression levels as compared to other methods, because of its ability to measure single cells and not just population averages.…”
Section: Figurementioning
confidence: 99%